ISLAMIC ETHICS IN SOCIAL MEDIA: A STUDY OF THE PHENOMENON OF CYBERBULLYING AND BODY SHAMING - La Ode Wahidin; Hasni Hasan; La Ode Aspin; La Ode Syukur (INJOSEDU: International Journal of Social and Education, 2025)
Social media has become an integral part of modern society. Behind its benefits, social media also presents various problems, including cyberbullying and body shaming. Both of these phenomena can have a negative impact on victims, both physically and mentally. This journal aims to examine Islamic ethics in social media, focusing on the phenomenon of cyberbullying and body shaming. The study is conducted by analyzing the verses of the Qur'an and Hadiths of the Prophet Muhammad SAW that are relevant to the ethics of communication and social interaction. The results show that Islam has clear ethical principles related to the use of social media. These principles emphasize noble morals, mutual respect, and maintaining privacy. Cyberbullying and body shaming are clearly against Islamic ethics because they hurt and degrade others. This journal also provides recommendations to prevent cyberbullying and body shaming on social media, such as increasing education about Islamic ethics, encouraging a culture of mutual respect, and strengthening regulations related to cyberbullying and body shaming.